Hubungan Terpaan Berita COVID-19 di Industri Penerbangan Pada Media Online dan Tingkat Kecemasan Tertular COVID-19 dengan Pengambilan Keputusan Menggunakan Jasa Transportasi Udara Masa New-Normal - Widya K. Siahaan; Joyo Nur Suryanto Gono; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
Before making a decision, the individual needs related information. Online media becomes the fastest means of finding information. In addition to cognitive aspects, individual affectives are also influential in the decision-making process. This study aims to find out the relationship between the exposure of COVID-19 news in the aviation industry in online media and the level of anxiety of contracting COVID-19 with decision making using new-normal air transportation services. Use the Theory of Persuasion